Ruptured lymphocele leading to lymphorrhea and wound dehiscence: A treatment approach with drainage and lymphangiography - Curtis Plante, BS; Nariman Nezami, MD; Jaime Pineda, MD; Christopher S. Morris, MD; Anant D. Bhave, MD; Bill S. Majdalany, MD (Radiology Case Reports)
A lymphocele is a collection of lymphatic fluid without epithelial lining, commonly occurring as a postsurgical complication. Most lymphoceles do not require treatment, but symptomatic lymphoceles can be successfully treated with surgery, percutaneous drainage and sclerotherapy, or lymphangiography with lymphatic embolization. Although drainage and sclerotherapy are effective in treating lymphoceles, their efficacy decreases in the setting of larger volume, ruptured, or multiseptated lymphoceles. Lymphangiography allows direct visualization of lymphatic vessels and identifies lymphatic leaks and guiding targeted interventions. Moreover, lymphangiography itself has therapeutic potential to directly treat lymphatic leakages. This case report describes a ruptured postkidney-transplant lymphocele, which dehisced the incision resulting in recalcitrant lymphorrhea. After drainage failed to resolve the lymphocele and sclerotherapy was deemed potentially risky to the kidney transplant, repeated lymphangiography sessions successfully treated the lymphocele and facilitated incisional healing.